2019
DOI: 10.1039/c9sm00500e
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of monodisperse hybrid gel particles with various morphologiesviaflow rate and temperature control

Abstract: We report a facile method for preparing monodisperse hybrid smart gel particles with various morphologies by using microfluidic devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The authors suggested that this approach could be used to assess the chemical compositions of different mixtures in droplet microreactors or to predict other fluid properties such as surface tension or viscosity; these parameters are important in the synthesis of a variety of microparticles. 13,[69][70][71][72][73][74] The prediction of fluid properties has also been approached from a different perspective. Mahdi and Daoud 51 demonstrated that a deep neural network can predict the droplet sizes in a water-in-oil emulsion by using the dimensionless capillary and Reynolds numbers of the two phases as inputs.…”
Section: The Convergence Of Microfluidics and Machine Intelligencementioning
confidence: 99%
“…The authors suggested that this approach could be used to assess the chemical compositions of different mixtures in droplet microreactors or to predict other fluid properties such as surface tension or viscosity; these parameters are important in the synthesis of a variety of microparticles. 13,[69][70][71][72][73][74] The prediction of fluid properties has also been approached from a different perspective. Mahdi and Daoud 51 demonstrated that a deep neural network can predict the droplet sizes in a water-in-oil emulsion by using the dimensionless capillary and Reynolds numbers of the two phases as inputs.…”
Section: The Convergence Of Microfluidics and Machine Intelligencementioning
confidence: 99%
“…Microbial growth depends sensitively on temperature. Temperature control has been developed previously in microfluidic platforms for biochemical reactions that require thermal cycling [50][51][52][53], such as the polymerase chain reaction (PCR), for the preparation of thermal-sensitive materials [54], and for the investigation of temperature-dependent biological processes such as oocyte membrane permeability in oocyte cryopreservation [55,56]. Heating and cooling, as well as sensing and feedback control, are important components of temperature control [57][58][59].…”
Section: Modeling the Physical And Chemical Environmentmentioning
confidence: 99%
“…Weitz et al. developed a facile droplet‐based method for the generation of monodisperse hybrid smart gel microparticles with various morphologies , as shown in Fig. 13A.…”
Section: Droplet‐based Microreactor For the Production Of Micro/nano‐mentioning
confidence: 99%
“…(ii‐iv) Optical images of hybrid gel particles with different morphologies at the representative temperatures. Reprinted from , copyright (2019) Royal Society of Chemistry. (B): (i) Droplets of polymer being generated inside a microcapillary device.…”
Section: Droplet‐based Microreactor For the Production Of Micro/nano‐mentioning
confidence: 99%